Environmentally friendly practices among restaurants: drivers and barriers to change - Kasim, Azilah; Ismail, Anida (Taylor & Francis Group, 2012)
This study of environmental management in the food service industry in general and the restaurant sector in particular highlights food services’ impacts on the environment, and drivers and barriers to change.The study is based on research in Penang, Malaysia, which included a personally assisted survey of 26 restaurant managers operating casual upscale businesses.The survey findings show that implementation of environmentally friendly practices is weak in the restaurant sector.While top managers claim to be informed and concerned about environmental issues, they are reluctant to invest in environmental management systems, to change practices, to advertise environmentally friendly products or invest in the implementation of environmentally friendly practices. They note barriers to change, including weakly enforced environmental laws and regulations, scarce and intermittent green supply chain, non-existent trade pressure and poor customer and community demand for restaurant business to implement green practices. A model of barriers and drivers leading to the implementation of environmentally friendly practices is presented in this study.Government intervention, including public education, capacity building and support in the trade and agricultural change to grow more organic crops, is suggested.The study depicts the responsiveness of restaurateurs towards the implementation of environmentally friendly practices in the context of a developing country.